2020
DOI: 10.1186/s12984-020-00732-z
|View full text |Cite
|
Sign up to set email alerts
|

Persons post-stroke improve step length symmetry by walking asymmetrically

Abstract: Background and purpose: Restoration of step length symmetry is a common rehabilitation goal after stroke. Persons post-stroke often retain the ability to walk with symmetric step lengths ("symmetric steps"); however, the resulting walking pattern remains effortful. Two key questions with direct implications for rehabilitation have emerged: 1) how do persons post-stroke generate symmetric steps, and 2) why do symmetric steps remain so effortful? Here, we aimed to understand how persons post-stroke generate symm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 47 publications
3
33
0
1
Order By: Relevance
“…Our results for the metabolic power of concurrent asymmetry in healthy participants may resolve previous paradoxical findings showing that metabolic cost in post-stroke walking is invariant to changes in step length asymmetry (Sánchez and Finley, 2018;Roemmich et al, 2019;Nguyen et al, 2020;Padmanabhan et al, 2020). We have shown that, when walking with concurrent asymmetry in step time, metabolic power is invariant to changes in step length asymmetry.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results for the metabolic power of concurrent asymmetry in healthy participants may resolve previous paradoxical findings showing that metabolic cost in post-stroke walking is invariant to changes in step length asymmetry (Sánchez and Finley, 2018;Roemmich et al, 2019;Nguyen et al, 2020;Padmanabhan et al, 2020). We have shown that, when walking with concurrent asymmetry in step time, metabolic power is invariant to changes in step length asymmetry.…”
Section: Discussionsupporting
confidence: 79%
“…Individuals walking post-stroke or with a prosthesis following lower-limb amputation frequently display spatiotemporal asymmetries (Isakov et al, 2000;Patterson et al, 2008). Asymmetry is often thought to contribute to the increased metabolic energy cost in pathological gait, but previous studies have found that metabolic cost is invariant to changes in step length asymmetry in post-stroke walking (Sánchez and Finley, 2018;Roemmich et al, 2019;Nguyen et al, 2020;Padmanabhan et al, 2020). In all studies to date, step time asymmetry or step length asymmetry has been enforced in isolation so that the nonconstrained gait parameter could vary freely.…”
Section: Introductionmentioning
confidence: 99%
“…Three articles did not meet the criteria because the studies either did not have a direct intervention to improve gait asymmetries or did not have a clinical diagnosis of gait asymmetry. As a result, 14 articles were included in the review [28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Study Search Selectionmentioning
confidence: 99%
“…Typical goals for gait rehabilitation programs for people post-stroke are to have the individuals walk more symmetrically (50,67). However, it's still an open question whether this goal could be considered the optimal way to walk for people post-stroke, with recent data suggesting that symmetrical step lengths do not improve measures of metabolic COT (23,25) and result in other kinematic and kinetic asymmetries (22). The results of our predictive simulations are consistent with these studies: when we enforced step length symmetry for the 0.75 m/s speed, the resulting gait pattern had significant step time asymmetry, with a small increase in metabolic COT.…”
Section: Clinical Implications For Post-stroke Rehabilitationmentioning
confidence: 99%
“…As such, some common rehabilitation interventions have targeted these spatiotemporal asymmetries to try to improve outcome measures of gait performance in people post-stroke. However, recent studies using biofeedback have shown little or no improvement in metabolic COT when people post-stroke walk with more symmetric step lengths (21)(22)(23)(24)(25). Therefore, it is still unclear how impairment interacts with observable gait deviations to cause the increase in metabolic COT in this population.…”
Section: Introductionmentioning
confidence: 99%